Changes in healthy infant gut microbiota over the past decades - Oksanen, Teo; Baizán-Urgell, Martina; Collado, Maria Carmen; Rautava, Samuli; Isolauri, Erika (Karger, 2026)
Introduction Bifidobacteria typify the gut microbiota of healthy, breast-fed infants. Altered gut microbiota composition in early infancy characterized by decreased Bifidobacterium abundance has been linked with a heightened risk of noncommunicable diseases. Our goal was to assess factors impacting on the gut microbiota composition in infants throughout the allergy and obesity epidemics of the past decades. Methods We studied deliveries from a series of clinical studies, grouped by the year of birth into three time periods (1997- 2001, 2005-2009, 2015-2022). Altogether 48 full-term breastfed infants’ having fecal samples available at the age of 1-3 months were studied for microbiota profiling by 16S rRNA gene amplicon sequencing. Perinatal factors including mode of birth and antibiotic exposure during pregnancy and at birth were taken into account. Results The richness and diversity of the infant gut microbiota decreased significantly over the three time periods. Reduced abundance of the phylum Actinobacteriota, and its genus Bifidobacterium was detected in children born in 2015-2022 as compared to those born during the time periods 1997-2001 and 2005-2009. The time period of birth was the strongest determinant of the gut microbiota composition, followed by maternal pre-pregnancy body mass index, antibiotic exposure during pregnancy and mode of birth. The relative abundance of members of the genus Bifidobacterium was significantly associated with elapsed time (1997-2022) and intrapartum antibiotic exposure. Conclusions The depletion of gut microbiota richness and diversity, and the selective reduction of relative abundance of the genus Bifidobacterium have occurred parallel to the increase in the prevalence of non-communicable diseases.